How to be a bourbon badass - Ruffenach, Linda (Red Lightning Books, 2018)
From tales of legendary master distillers to food and drink recipes for classics like the bourbon highball and fresh twists like bacon-wrapped dates with a bourbon glaze, Linda Ruffenach will redefine your perceptions of bourbon and those who savor it. Your journey to becoming a bourbon badass begins here.